Effect of pelvic floor electrical stimulation on diaphragm excursion and rib cage movement during tidal and forceful breathing and coughing in women with stress urinary incontinence: A randomized controlled trial - Hwang, Ui-jae (Medicine (Baltimore), 2021)
BACKGROUND: The pelvic floor muscle (PFM) is associated with respiratory function. We investigated the effects of PFM training by pelvic floor electrical stimulation (PFES) on PFM strength, diaphragm excursion, and upper rib cage movement during tidal and forceful breathing and coughing in women with stress urinary incontinence (SUI). METHODS: In total, 33 participants with SUI were divided into PFES and control groups. The two groups were measured pre- and post-8 weeks of training. Diaphragm excursion and upper rib cage movement during tidal and forceful breathing and coughing and PFM strength were measured using sonography, electromagnetic sensors, and perineometry. RESULTS: There were significant difference of main effect between pre- and post-training and between groups in PFM strength (between groups: P = .001, between time: P < .001) and diaphragm excursion during forceful breathing (between groups: P = .015, between time: P = .026) and coughing (between groups: P = .035, between time: P = .006). There were significant differences in diaphragm excursion during tidal (P = .002) and forceful breathing (P = .005) and coughing (P < .001) between pre- and post-training in the PFES group. Elevation of the upper rib cage during tidal (P < .001) and forceful breathing (P = .001) was significantly decreased after 8 weeks of training in the PFES group. Widening in the horizontal plane in the upper rib cage during forceful breathing (P < .001) was significantly increased after 8 weeks of training in the PFES group. PFM strength (P < .001) was significantly increased after 8 weeks of training in the PFES group. CONCLUSIONS: Pelvic floor muscles training by electrical stimulation can improve diaphragm excursion and breathing patterns in women with SUI.